Historical Overview of Cuba’s Costs of Sugar Production 1959-2005 - G. B. Hagelberg; José Alvarez (EDIS)
This is EDIS document FE626, a publication of the Food and Resource Economics Department, Florida UF/IFAS Extension, Gainesville, FL. Published March 2006. Reviewed January 2015.